HUBUNGAN ANTARA KETEGUHAN GESER DENGAN KETEGUHAN REKAT INTERNAL PAPAN PARTIKEL - Paribotro Sutigno; I M Sulastiningsih (Jurnal Penelitian Hasil Hutan, 1992)
One of  the  partideboard  properties that  must be tested  is internal  bond  strength  or tensile  strength  perpendicular to surface. the  testing  procedure is relatively  difficult   because  before  applying  a tension  load vertically  to the  board  face, the  specimen  must   be  adhere  to  steel  or  wood   blocks  for  seuerol hours  to obtain  good  adhesion.  To  simplify   the pro- cedure, the  use  of  another   testing procedure called shear  strength   test  was tried.  It  is found   that  there  is  a relationship between   shear strength   (X)  and  internal  bond  strength   (Y)   which  can  be expressed   by   linear  regression  equations  i.e,: Y  = -  0.105  +  0.180   X  for  interior  particleboard  and  Y =  -  0.925  + 0.398  X  for  exterior  particleboard.   The  interior particleboard  specimens were  tested   under  dry   condition  whereas  exteriorparticleboard  specimem were boiled  for  two hours  before  testing.  Both regression equations can not  be pooled,  Based  on  the  result  it can be cohcluded  that  internal bond  strength   of  particleboard  can  be estimated by  using  its shear strength value.